The Challenge of Implementing The Merdeka Campus Program Policy In The Covid-19 Pandemic Period - Paramitha, Yulia Della; Oktaviana, Prita Veronica Putri; Fauzia, Salsabila Azzahra; Kismartini, Kismartini; Herawati, Agustin Rina (International Journal of Social Service and Research, 2021)
Education in the 4.0 revolution era is an innovation (student centered) to strengthen creativity and mentality in facing challenges. The challenges during the Covid-19 pandemic require education to use technology assistance. Therefore, the Minister of Education and Culture, Nadiem Makarim, established the Merdeka Campus program policy as a strategic plan for the development of national education. In an effort to implement the Merdeka Campus program, of course, there are challenges during the Covid-19 pandemic. The method used in writing this article is a qualitative approach with the library method. Therefore, the author wants to examine more deeply about the analysis of the challenges of implementing the Merdeka Campus program policy during the Covid-19 pandemic